Estudo epidemiológico e molecular de portador nasal de Staphylococcus aureus e de Staphylococcus aureus meticilinaresistente em Pronto Atendimento Pediátrico e em Unidades de Terapia Intensiva Neonatal de Goiânia - VIEIRA, Maria Aparecida da Silva (2010)
Nasal carriage of Staphylococcus aureus methicillin-resistant (MRSA) is known to be a risk for subsequent infection. The MRSA carriers are an emergent and hidden reservoir in community and in the health-care environment. The aim of this investigation were to assess the prevalence and risk factors for MRSA nasal carriage in children attending emergency departments (ED) and Neonatal Intensive Care Units (NICU), and to describe the molecular features of such isolates. Methods: Nasal swabs were obtained from children less than 60 months of age attending ED, and from newborns of the four NICUs of Goiânia city, central Brazil, in 2007 and 2008. The definition of MRSA followed the CLSI criteria. Exposure variables to S. aureus and MRSA carriers were gathered through in-person interviews with mothers and hospital records. Univariate and multivariate logistic regression were performed to identify risk factors for S. aureus and MRSA carriage. Molecular typing was evaluated by pulsed field gel electrophoresis, staphylococcal cassette chromosome mec (SCCmec) typing, and multilocus sequence type (MLST). Results: A total of 2,735 children were enrolled. At the ED (n=2.034), the prevalence respectively of nasal carriages for S. aureus and MRSA were 20% (n=408) and 0.2% (n=4). Among NICUs (total of infants = 701), the prevalence of nasal carriage ranged from 0.03% to 15.7% for S. aureus and, from 0.0% to 2.0% for MRSA. At the ED, MRSA carriage was independently associated with child-care attendance in the previous 6 months (OR=10.6; p=0.045) and congenital malformation (OR=26.8; p=0.002). All nasal carriers at NICUs were from private hospitals. Only length of hospitalization was associated with MRSA nasal carriage at NICUs (p=0.023). Among four MRSA nasal carrier at ED, one harbored SCCmec type III, and three SCCmec type IV. Among four children from at the NICUs two infants harbored SCCmec type III, and two SCCmec type IV. All MRSASCCmec type III were multidrug-resistants. Strains related to Pediatric/USA800 and Brazilian MRSA clones were detected in both, ED and NICUs. One MRSA cluster related to Western Australia/USA400 was detected in ED. Conclusions: Children visiting ED, especially those reporting day-care attendance, and neonates from NICUs may play a role in spreading MRSA in healthcare settings. The study suggests cross transmission of MRSA type III and type IV between ED and hospital environments.